Nanozymes in Medicine - Daima, Hemant Kumar; PN, Navya; Lichtfouse, Eric. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book reviews the latest advances and biomedical applications of nanozymes, which are artificial nanomaterials exhibiting enzymatic properties similar to natural enzymes, but with less limitations than natural enzymes. Nanozymes display advantages such as facile synthesis, easy surface modification, improved stability, higher catalytic power, and target-specific binding. Nanozymes containing metals, metal oxides, carbon, and metal sulfide are actually used for cancer therapy, biomolecules sensing, bioimaging, disease diagnostics and diabetes management. The book discloses underlying mechanisms, concepts, recent trends, constraints, and prospects for nanomedicine using nanozymes.
Chapter 1 Nano cerium oxide in medicine, agriculture and the industry -- Chapter 2 Synthesis and sensing applications of peroxidase-mimic nanozyme -- Chapter 3 Nanozymes for glucose sensing and diabetes management -- Chapter 4 Nanozymes for bioimaging and disease diagnostics -- Chapter 5 Nanozymes for improving anticancer therapy -- Chapter 6 Enzyme-based nanomedicine for cancer therapy -- Chapter 7. Synthesis of two-dimensional metal, metal oxide and metal hydroxide nanomaterials for biosensing -- Chapter 8 Biological applications of nanozymes.
Keywords: Nanobiotechnology; Medicinal chemistry; Catalysis; Nanobiotechnology; Medicinal Chemistry; Catalysis